Nghiên cứu sự phân hủy in vitro của polylactit - Tiến, Mai Văn; Trinh, Phạm Thế (Vietnam Journal of Chemistry, 2014)
In this study arange of homopoly(lactide) were synthesized by bulk copolymerization and subjected to in vitro hydrolytic degradation. In vitro degradation studied was conducted at 37oC in pH 7.4 phosphate buffered saline. The effect of lactide type and molecular weight on biodegradable of PLA was studied. The degradation products form in the saline buffer solutions further characterized by SEM, IR, 1H-NMR; 13C-NMR and GC-MS.